Tibial osteosynthesis in a guinea pig (Cavia porcellus) - Macedo, A. S. [UNESP]; Goulart, M. A.; Alievi, M. M.; Mombach, V. S.; Dal-bó, Í. S.; Mucillo, M. S.; Silva, R. B.; Minto, B. W. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
A guinea pig was presented with left pelvic limb lameness after unknown trauma. Radiographs revealed complete oblique diaphyseal fracture of the distal third of the left tibia and fibula. The guinea pig was treated surgically with an intramedullary pin. The day after surgery the guinea pig was using the limb comfortably (grade 1/5 lameness). Callus formation was obtained 21 days after surgery without complications.

Um cobaio foi atendido com claudicação de membro pélvico esquerdo após trauma desconhecido. Radiografias revelaram fratura completa oblíqua da diáfise do terço distal da tíbia e fíbula esquerdas. O cobaio foi tratado cirurgicamente com um pino intramedular. No dia seguinte à cirurgia, o paciente utilizava o membro confortavelmente (grau 1/5 de claudicação). Calo ósseo foi obtido 21 dias após a cirurgia, sem complicações.
Osteossíntese de tíbia em um cobaio (Cavia porcellus)
Keywords: Wild animals; Kirschner wires; Tibia; Fracture; Animais silvestres; Fios Kirschner; Tíbia; Fratura